Apresentação PBCIB n.2, v.11, 2016. - Freire, Gustavo Henrique de Araújo; Freire, Isa Maria; Araújo, Vânia Rodrigues Hermes de (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2016)
Apresentação PBCIB n.2, v.11, 2016.